Membangun Learning Society di Perguruan Tinggi melalui Perpustakaan - Basuki, Basuki (STAIN Ponorogo, 2009)
Stratgic alteration which is perfomed by ministry of national education concerning the strategic planning of higher education 2003-2010 causes direct consequences to the visions and mission, the output target, th organization management and th standardization at all aspects.